Investigating the antioxidant potential, toxicity, and hypocholesterolemic effects of kop nut in a high-fat diet-induced type 2 diabetes rat model - Zamzuri, Nur Zakiah Amani (2023)
Type-2 diabetes mellitus (T2DM) is usually associated with obesity, with the increased production of free fatty acids and insulin resistance. In this study, the toxicity and therapeutic potential of Ostodes pauciflora Merr or Kop nuts oil extract as a cholesterollowering agent in a T2DM rat model, was explored. The antioxidant activity of different Kop nut oil extracts was evaluated using a DPPH assay. It revealed high inhibition percentage of DPPH radical at the lowest concentration (10 μg/mL) where diethyl ether extract inhibits at 61.44%, followed by petroleum ether extract at 60.58%, and lastly, hexane extract with 59.33%. In acute toxicity, each five (n = 5) male Sprague Dawley (SD) rats were given different dose of Kop nut oil extract and were administered once only throughout the study according to the OECD 425 protocol. Based on these observations, the toxic dose of Kop nut extract is estimated to exceed 2000 mg/kg. In this pilot study, twelve (n = 12) male SD rats were used in the subacute study to evaluate the cholesterol-lowering properties of Kop nut oil extract. After giving treatment for 4 weeks, all groups show no significant changes in blood glucose and cholesterol levels. Other than that, the histological examination shows restoration of hepatic cells with an improved architecture in the Metformin and Extract group compared to the Untreated group (diabetic rats), such as less formation of macrovesicular and microvesicular. The finding indicates that Kop nut oil extract poses an antioxidant potential with LD50 above 2000 mg/kg while showing improvement in liver histology.